Analysis of purchasing decisions using online pre-order system at Shopee - Fitriani; Yuli Asbar; Widyana Verawaty Siregar (Operations Management and Information System Studies, 2021)
This study aims to analyze the factors that influence the purchase decisions of the online pre order system at Shopee online shop in Lhokseumawe city. This study uses primary data obtained by distributing questionnaires to 100respondents selected using the purposive sampling method. The data analysis method used is multiple linear regression analysis with the help of SPSS 24. The results of the study partially show that price, convenience, trust, and reputation have a significant effect on purchase decisions with the pre-order system at the online Shopee in Lhokseumawe city. Simultaneously, price, convenience, trust, and reputation also have significant effect on the purchase decisions with the pre-order system on the Shopee online shop in Lhokseumawe city.